Composition and enzymatic activity in bulk milk from dairy farms with conventional or robotic milking systems. Issue 2 (19th May 2017) - Johansson, Monika; Lundh, Åse; de Vries, Ruben; Sjaunja, Kerstin Svennersten
Abstract : The objective of the studies reported in this research communication was to investigate differences in composition and enzymatic activities in bulk milk samples provided from Swedish dairy farms with different management systems, i.e. automated (AMS) and conventional milking systems (CMS). A bulk milk sample was collected from each of 104 dairy farms, 51 using AMS and 53 using CMS, located in the same geographical region. Sampling took place within two consecutive days during the indoor period (October). Milk samples were analysed for contents of total fat and protein, free fatty acids (FFA), caseins and whey proteins, somatic cell count (SCC), pH, plasmin and plasminogen derived activities, and total proteolysis. Our results showed a lower protein content and higher SCC in bulk milk from AMS herds compared with milk from CMS herds. Plasmin, plasminogen and total plasmin/ plasminogen derived activities were lower in milk from AMS herds but despite this, total casein and the ß-casein fraction as % of total protein were lower in milk from AMS herds than in milk from herds using CMS. Total proteolysis was higher in milk from AMS herds, suggesting that other proteases than plasmin, e.g. cellular and bacterial proteases, contributed to the degradation of casein. This was supported by a positive correlation between SCC and total proteolysis ( P < 0·01), as well as a negative correlation between total proteolysis and ß-casein fraction ( P < 0·05). In conclusion, comparing the quality of bulk milk from commercial dairy herds using AMS and CMS, respectively, several differences were observed, suggesting a significant effect from management system.